Migrated Tubal Ligation (Filshie) Clip as an Uncommon Cause of Chronic Abdominal Pain. (10th February 2020) - Sharma, Sahil; Martyniak, Radek; Khokhotva, Vladislav
Abstract : Tubal ligation (TL) is an effective and common method of fertility control. In the year 2009, over 24, 000 were performed in Canada alone. Migration of Filshie clips used during TL is estimated to occur in 25% of all patients; 0.1-0.6% of these patients subsequently experience symptoms or extrusion of the clip from anatomical sites such as the anus, vagina, urethra, or abdominal wall. Migrated clips may present as chronic groin sinus, perianal sepsis, or chronic abdominal pain. These symptoms can occur as early as 6 weeks or as late as 21 years after application. We present the case of a 49-year-old female with a 3.5-year history of intermittent dull nonradiating left upper quadrant (LUQ) pain lasting on average 2-3 days. There were no other associated symptoms, and the longest pain-free period was 4 days. Her past medical history includes COPD, GERD, IBS, and depression. Current medications are only remarkable for Symbicort. Pertinent past surgical history includes laparoscopic tubal ligation with Filshie clips in 1999, followed by a vaginal hysterectomy in 2013. Migrated tubal ligation clip was noted on an abdominal X-ray. The patient was then referred for surgical management. Subsequent CT scan confirmed a solitary clip present adjacent to the left lobe of the liver. No other abnormalities were reported. Patient underwent laparoscopy for removal of the clip, which was identified to be underneath the left lobe of the liver embedded in the gastrohepatic omentum. Please see the video link provided. Postoperative pathology report confirmed the presence of a Filshie clip. Patient reported complete resolution of her LUQ pain at a 5-week and 3.5-month follow-up. This case shows that although symptomatic clip migration is a rare phenomenon, it should be given special consideration in women with unexplained chronic abdominal pain and a history of TL. Additionally, removal of clip can provide resolution of symptoms.